Comparison of S.T.O.N.E score with Guy’s stone score as a tool to predict stone clearance rates in patients undergoing percutaneous nephrolithotomy: a single center study - Handa, Anoop; Dash, Sharat Chandra; Solanki, Nimit; Shukla, Abhishek; Singh, Gagandeep; Jha, Aditya Abhishek; Khandelwal, Sachin (International Surgery Journal, 2020)
Background: We aimed to compare the Guy’s stone score and S.T.O.N.E nephrolithometry score and assess their predictive accuracy for percutaneous nephrolithotomy (PCNL) outcomes. Methods: A total of 100 patients, who underwent PCNL between Jan 2018 and Dec 2018 were included in the study. All patients were evaluated with computerized tomography (CT) scan preoperatively and scores were calculated. Patient demographic characteristics, intraoperative and postoperative variables were evaluated. The relationship between the Guy’s and S.T.O.N.E scores, and their prediction for postoperative stone-free status, complications were compared. Results: The mean Guy’s score was 2.04±1.01, and the mean S.T.O.N.E score was 8.0+1.7. The mean operative time was 101.9+41 minutes and the mean blood loss was 170+113ml. The complication rate in our study was found to be 32%, majority were grade 1-2. Both scoring systems showed positive correlation with stone burden, operating time and blood loss. The overall stone free rate was 72% and both the GSS and S.T.O.N.E score were significantly associated with success of the procedure. Conclusions: Both Guy’s and S.T.O.N.E scoring systems are equally effective in predicting stone-free status.